Chemical and Organoleptic Characteristics of Sambal Ronto - Rita Khairina; Iin Khusnul Khotimah; Muhammad Yazid; Rizky Fadliani (Universitas PGRI Semarang, 2020)
This research studied the chemical and organoleptic characteristics of sambal ronto at various spice concentrations. Sambal ronto is a typical chili sauce from the coastal community of South Kalimantan which is made from ronto mixed with spices and sautéed with cooking oil. The spices used are chilies, shallots, garlic, lemongrass, laos, bay leaves, and palm sugar. The research was conducted with a completely randomized design. The treatments consisted of concentrations of ronto and spices ratio, (1: 1) O, (1: 2) A, (1: 3) C, and (1: 4) D. The proximate test consists of water, ash, protein, fat, carbohydrate (by different) content, and pH. The organoleptic test was carried out by testing the preference for the parameters of color, aroma, texture, taste, and appearance. The results showed that the best ronto: spice ratio was treatment B (1: 3). The chemical characteristics of the best sambal ronto are 44.21% moisture content, 4.20% ash content, 5.92% protein content, 14.47% fat content, carbohydrate content (31.22% by different) and pH 4.79. Organoleptic values for the parameters of color, aroma, texture, taste, and appearance were 4.5, 4.9, 4.9, 4.5, and 4.8, respectively. All parameters indicate a value close to very like.